Finite frequency fault estimation observer design for T-S Fuzzy discrete-time descriptor systems. Issue 15 (17th November 2020) - Liu, Yimin; Chen, Jianliang; Chu, Hongjun; Li, Juan
Abstract : This paper deals with the problem of H ∞ fault estimation observer design for T-S fuzzy nonlinear discrete-time descriptor systems in the finite frequency domain. First, a novel fault estimation observer for the augmented descriptor system is given. Based on Parseval's theorem and Lyapunov theory, the performance in the finite frequency domain is derived via time-domain method. Then, new sufficient conditions of admissibility and robust performance index for the dynamic error system are obtained as bilinear matrix inequalities. Meanwhile, an iterative linear matrix inequality algorithm is given to obtain the optimal solution. Finally, an example is given to demonstrate the effectiveness of our method.